(untitled) (Nativa, 2018)
O objetivo deste estudo foi analisar a variação da estrutura diamétrica de uma comunidade arbórea em floresta densa de terra firme e dos principais grupos de espécies de estágios iniciais e tardios de sucessão, bem como caracterizar a estrutura vertical da floresta. Em 2016, foram inventariadas todas as árvores com DAP ≥ 10 cm e mensuradas suas alturas. Em 2017, as árvores foram reamostradas. A estrutura diamétrica foi analisada por meio do quociente “q” De Liocourt para: a comunidade, principais espécies de maior VI e os grupos ecológicos (GE). A análise da estrutura vertical da vegetação foi feita pela distribuição do número de árvores nos estratos, utilizando-se três métodos: (I) – Sanquetta (1995), (II) - Souza (1990), e (III) – Souza et al. (2003). A estrutura diamétrica da comunidade e dos GE no período avaliado foi caracterizada por árvores de pequeno porte nas menores classes de diâmetro. O Método II não trouxe bons resultados sobre o comportamento das espécies no estrato médio por apresentar fortes tendências em concentrar um maior número de indivíduos nesse estrato. Os resultados da estrutura altimétrica e diamétrica demonstraram indicativos que a exploração antrópica no passado alterou a estrutura da floresta. Palavras-chave: espécies amazônicas, “q” De Licocourt, estratificação, incremento. STRUCTURE AND DYNAMICS IN A DENSE OF TERRA FIRME FOREST, SOUTHEAST OF AMAPÁ, BRAZIL ABSTRACT: The study aimed to analyze the variation of the diameter structure of a arboreal community in a dense terra firme forest and the main groups of species of early and late stages of succession, as well as characterize the vertical structure of the forest. In 2016, all trees with DBH ≥ 10 cm were inventoried and their heights measured indirectly. In 2017, the trees were re-measured. The diametric structure was analyzed using the "q" De Liocourt quotient for: the community, major species of higher (VI) and ecological groups (EG). The analysis of the vertical structure of the vegetation was made by the distribution of the number of trees in the strata, using three methods: (I) – Sanquetta (1995), (II) - Souza (1990), and (III) – Souza et al. (2003). The diametric structure of the community and the EG during the period evaluated was characterized by small trees in the smallest diameter classes. Method II did not bring good results on the behavior of the species in the middle stratum because it presents strong tendencies to concentrate a greater number of individuals in this stratum. The results of the altimetric and diametric structure have demonstrated that antropic exploration in the past has altered the structure of the forest. Keywords: amazonian species, “q” De Licocourt, stratification, increment.